Vertical structure and strategic environmental trade policy - Hamilton, Stephen F.; Requate, Tilman (CESifo working papers, 2001)
The idea that environmental trade policy may be used to achieve competitive advantage in international markets has important implications for the way we conceive tree-trade. This paper reconsiders the issue of strategic environmental policy in a model that makes explicit the vertical structure that supports production of the traded good. We find these intranational vertical relationships to have a substantial qualitative effect on the optimal strategic environmental trade policy. We show that under both quantity and price competition in the international market, the optimal policy to levy on the polluting input when vertical contracts are allowed is a Pigouvian tax.